Intra- and interspecific interactions among Tribolium castaneum and Cryptolestes ferrugineus in stored wheat at different insect densities - Hulasare, Raj; White, Noel; Jayas, Digvir; Demianyk, Colin (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2003)
SummaryCryptolestes ferrugineus and Tribolium castaneum are important economical pests of stored grain in Canada. Insects were reared separately or together on hard red spring wheat at three insect densities representing 1000, 500, and 250 adults per kilogram of wheat for single species and twice that of single densities for mixed species, in the laboratory (30°C, 70% RH). The experiment was conducted on dry (12% moisture content [MC], wet basis) and damp wheat (15% MC, wet basis). Adults were sampled every 2 weeks over a 10-week period. Sifted wheat was incubated at 30°C, 70% RH for 4 weeks to observe the number of adults emerging from immatures present under the seed coat of the wheat germ. All experiments were replicated four times. Initial insect densities, moisture content, and species combination had significant effects on the resulting adult population. Adult numbers for both species were higher on 15% MC wheat. In 12% MC wheat, T. castaneum numbers were higher than C. ferrugineus numbers when reared separately whereas this was reversed in 15% MC grain. Cryptolestes ferrugineus populations were significantly higher when reared with T. castaneum than when reared as a single species on 12% MC grain. The trend was reversed in 15% MC grain. At both grain moistures, T. castaneum numbers were higher as an isolated species compared to when reared with C. ferrugineus. The study suggested that T. castaneum populations were inhibited in the presence of C. ferrugineus. High insect density often accentuated these effects.